THE USE OF MICRONIZED VEGETABLE AND FRUIT POWDERS IN THE TECHNOLOGY OF PASTA - Svetlana Yakovlevna Koryachkina; Ekaterina Nikolaevna Kholodova; Valerij Yakovlevich Chernykh; Olga Leonidovna Ladnova (Современная наука и инновации, 2022)
This paper examines the possibility of using tokodispersnogo vegetable and fruit powders produced in-novative disintegration drying method at a temperature of 40 °C, allowing you to save beneficial ingredients of raw materials, in the production of pasta with the purpose of increasing the nutritional value. The use of powders of vegetables and fruits in the production of pasta will expand the range of food.